Effect of pectin oligosaccharides and zinc chelate on growth performance, zinc status, antioxidant ability, intestinal morphology and short‐chain fatty acids in broilers. Issue 3 (22nd February 2019) - Wang, Zhongcheng; Yu, Huimin; Xie, Jingjing; Cui, Hu; Gao, Xiuhua
Abstract: A 42‐day trial was conducted to investigate the effect of pectin oligosaccharides (POS) and zinc chelate (Zn‐POS) on growth performance, antioxidant ability, zinc status, intestinal morphology and short‐chain fatty acids in broilers. A total of 324 1‐day‐old Arbor Acres broilers were randomly assigned to three treatments with six cages of 18 chicks. Treatments were: (a) Control, 80 mg/kg Zn from ZnSO4 ; (b) POS, 80 mg/kg Zn from ZnSO4 + 482 mg/kg POS (the same amount of POS as treatment 3); and (c) Zn‐POS, 80 mg/kg zinc from Zn‐POS. Compared to the Control, both POS and Zn‐POS supplementation increased average daily gain and reduced the mortality during day 22–42, and only Zn‐POS supplementation decreased the ratio of feed to gain during day 22–42 and 1–42. Moreover, both POS and Zn‐POS supplementation improved Zn status and gut function as evidenced by increased metallothionein concentrations in the pancreas, villus height in the duodenum and isobutyrate concentrations in the caecal digesta. Additionally, Zn‐POS supplementation increased gene expressions of metallothionein, Zn transporter 1, Zn transporter 2 in the pancreas, nuclear factor erythroid 2‐related factor 2 in the liver, the concentrations of acetate, propionate, butyrate and total SCFA in the caecal digesta and the villus height to crypt depth ratio in the duodenum and jejunum, whereas decreased the crypt depth in these two tissues. Altogether, our results revealed that dietary POS or Zn‐POS supplementation benefited growth performance, Zn status, antioxidant ability and gut function of broilers. Supplementing Zn‐POS in the form of chelate was more effective than feeding POS or ZnSO4 separately.